MATHEMATICAL PROFICIENCY: AN ANALYSIS OF PROSPECTIVE TEACHERS' ABILITY TO SOLVE MATHEMATICAL PROBLEMS - Elvi, Mariyanti (LPPM Universitas Muhammadiyah Bulukumba, 2025)
Mathematical proficiency is a determinant of students' success in mathematics learning. This research aims to describe the mathematical skills of prospective teacher students, so that they can reflect and take follow-up actions to improve their mathematical skills as preparation for teaching and educating students in schools. The type of research used is descriptive research with a qualitative approach.. The research subjects are second-year prospective teacher students, totaling 35 people. This research measures 4 strands of mathematical proficiency: (1) conceptual understanding, (2) procedural fluency, (3) strategic competence, and (4) adaptive reasoning. The research results indicate that students' mathematical proficiency is still relatively low, especially in conceptual understanding, procedural fluency, and strategic components. Meanwhile, the indicator of adaptive reasoning is categorized as moderate.